2014
DOI: 10.1177/1403494814550680
|View full text |Cite
|
Sign up to set email alerts
|

District nurses’ preventive home visits to 75-year-olds: An opportunity to identify factors related to unsafe medication management

Abstract: Preventive home visits seem to provide a unique opportunity to promote safe medication management. Several factors related to unsafe medication management were identified, and several different nursing care interventions were carried out to ensure safe medication management. Use of the SMA tool in preventive home visits seems to be advantageous in improving the safety of medication management among older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 30 publications
2
29
0
3
Order By: Relevance
“…This study is limited to one region in a Norwegian context. However, many of the findings are comparable with other PHV studies like Lagerin et al 38 and Sherman et al; 45 so, the results should be applicable to PHV models in countries or regions other than Norway.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study is limited to one region in a Norwegian context. However, many of the findings are comparable with other PHV studies like Lagerin et al 38 and Sherman et al; 45 so, the results should be applicable to PHV models in countries or regions other than Norway.…”
Section: Discussionsupporting
confidence: 83%
“…In a Swedish PHV study among 75-year-olds, 42.5% had polypharmacy (used five or more drugs). 38 A notable finding was that no use of alcohol was associated with increased risk for polypharmacy. In a group of home dwelling persons over 80 years, 58% had polypharmacy (≥5 medications) and it was found that those who did not use alcohol had a higher risk for polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…In nursing practice we also have effective technology for nurses. Nurses are often in hurry, so applications can help them in decision-making [16] and documentation [13] and in clinical work [17]. We take care of the clients as possible and with the help of updated information.…”
Section: Ethical Values and Digitalizationmentioning
confidence: 99%
“…The district nurse (DN), also commonly labelled Advanced Practice Nurse (APN) in Primary Health Care with a multidisciplinary PHC background, together with midwifes plays an important and autonomous role in the Swedish PHC system [ 22 ]. In Swedish PHC, DN and midwives meet women aged 45–55 years with concerns about their bodily changes and psychological symptoms [ 23 ].…”
Section: Introductionmentioning
confidence: 99%